2024
DOI: 10.18063/ijb.v4i1.129
|View full text |Cite
|
Sign up to set email alerts
|

Novel ultrashort self-assembling peptide bioinks for 3D culture of muscle myoblast cells

Abstract: The ability of skeletal muscle to self-repair after a traumatic injury, tumor ablation, or muscular disease is slow and limited, and the capacity of skeletal muscle to self-regenerate declines steeply with age. Tissue engineering of functional skeletal muscle using 3D bioprinting technology is promising for creating tissue constructs that repair and promote regeneration of damaged tissue. Hydrogel scaffolds used as biomaterials for skeletal muscle tissue engineering can provide chemical, physical and mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Other myogenic markers that are commonly used to visualize and assess myotube formation, include desmin [ 82 , 103 ] and α-sarcomeric actin [ 82 , 85 , 88 , 89 , 101 ]. In addition, a cytoskeletal actin stain can be utilized to assess overall biomaterial-guided cell alignment [ 50 , 70 , 72 , 76 , 84 , 87 , 98 ].…”
Section: Methods For Assessing Skeletal Muscle Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other myogenic markers that are commonly used to visualize and assess myotube formation, include desmin [ 82 , 103 ] and α-sarcomeric actin [ 82 , 85 , 88 , 89 , 101 ]. In addition, a cytoskeletal actin stain can be utilized to assess overall biomaterial-guided cell alignment [ 50 , 70 , 72 , 76 , 84 , 87 , 98 ].…”
Section: Methods For Assessing Skeletal Muscle Regenerationmentioning
confidence: 99%
“…To overcome this shortcoming, Arab et al. used printable, self-assembling peptides to create 3D hydrogel constructs to promote myogenic differentiation [ 87 ]. The authors found that cells within their peptide hydrogels aligned in response to the structural cues provided by their synthetic peptides, while cells grew in a random orientation in their alginate-gelatin controls.…”
Section: Biomaterials Therapiesmentioning
confidence: 99%
“…Recently, Arab et al used two tetra-peptides, CH-01 and CH-02, as bioinks for 3D culture of C2C12 mouse myoblasts. 71…”
Section: Ultrashort Peptides For Bioprintingmentioning
confidence: 99%
“…Due to their amphiphilic character and their innate tendency to self-assemble in water, they form rapidly nanofibrous scaffolds in an aqueous solution in forms of soft solid and transparent hydrogels. The natural but synthetic character of these self-assembling peptides renders them as appealing bioinks for bioprinting[ 8 ]. Peptides are generally known for their biocompatibility, biodegradability, and suitability for cell growth[ 9 ].…”
Section: Introductionmentioning
confidence: 99%